Analysis of the Measurement of the Khanza Hospital Information System (SIMRS) at RSIA Graha Kurnia Using the Human Organization Technology (HOT-Fit) - Ardi Prianto; Handoyo Widi Nugroho (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2025)
This study evaluates the effectiveness of the Khanza Hospital Information System (SIMRS) at RSIA Graha Kurnia using the Human Organization Technology Fit (HOT-FIT) model. The aim is to understand the relationships between key constructs such as System Quality (SQ), Information Quality (IQ), Service Quality (SerQ), Organizational Environment (OE), System Use (SU), User Satisfaction (US), and Net Benefit (NB). A survey was conducted with 56 respondents from various departments within the hospital using a self-administered questionnaire. The study employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the data. The results indicate that System Quality (SQ) and Information Quality (IQ) significantly influence System Use (SU) and User Satisfaction (US), which in turn contribute to the Net Benefit (NB) of SIMRS. Additionally, the Organizational Environment (OE) plays a vital role in enhancing the overall benefits derived from the system. These findings emphasize the importance of improving system quality, ensuring the availability of accurate and relevant information, and fostering a positive organizational environment to maximize the effectiveness of the SIMRS. The study concludes that improving System Quality and Information Quality should be prioritized to increase both System Use and User Satisfaction, ultimately leading to greater Net Benefit for the hospital. The findings contribute valuable insights into how the HOT-FIT model can be applied to enhance hospital information systems, offering actionable recommendations for healthcare institutions seeking to optimize their information systems' performance.